2009
DOI: 10.1111/j.1528-1167.2009.02220.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalography in Landau‐Kleffner syndrome

Abstract: SUMMARYMagnetoencephalography (MEG) detects weak magnetic fields outside the head. Spikes generated on the perisylvian convexity are detected only by electroencephalography (EEG), whereas spikes with intrasylvian generators are selectively seen by MEG. Generators of MEG and EEG spikes are determined using equivalent current dipoles (ECDs) that represent local cortical activity in parallel pyramidal neurons. MEG localizes cortical spike generators with a 1-2-cm spatial accuracy, and with a millisecond time reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Intrasylvian onset suspected MEG can detect intrasylvian spikes in EEG-negative patients [19] or may identify a single intrasylvian epileptogenic focus even when the EEG abnormalities are widespread, e.g., in LKS [20,21,23,51].…”
Section: Clinical Scenario Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrasylvian onset suspected MEG can detect intrasylvian spikes in EEG-negative patients [19] or may identify a single intrasylvian epileptogenic focus even when the EEG abnormalities are widespread, e.g., in LKS [20,21,23,51].…”
Section: Clinical Scenario Commentsmentioning
confidence: 99%
“…Evoked potentials from Heschl's gyrus are detectable even to the level of tonotopic mapping with millimeter precision [2]. Posterior intrasylvian spikes are detectable in 68-100% of patients with Landau-Kleffner syndrome [20][21][22], and MEG-directed surgery can result in dramatic clinical improvement [21,23]. • Interhemispheric fissure: MEG sensitivity is good for a length of cortex that extends about 1/3rd of the way to the corpus callosum from the convexity (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, abnormal epileptiform discharges have been shown to be associated with transient cognitive impairment [2]. Cortical reorganization in response to continuous epileptiform activity has been suggested, which would account for residual language problems [4,23,26,27]. One theory postulates that near-continuous epileptiform activity hampers synaptic pruning [28,29], although volumetric studies do not necessarily support this conclusion [30].…”
Section: Rehabilitation Issues In Landau-kleffner Syndromementioning
confidence: 89%
“…Some autoantibodies to brain endothelial cells have been found to be present at higher levels in some children with LKS than in healthy controls [21] and the sera of children with LKS tested for anti-brain antibodies have shown greater reactivity against the cerebellum, auditory cortex and brainstem as compared to those of healthy controls [22], suggesting immune involvement. As previous research has shown that language function can be preserved with only one hemisphere, it seems clear that LKS causes bilateral involvement, either independently or induced by the primary hemisphere [12,23]. Bilateral epileptic discharges are generated in the perisylvian cortex, which is related to auditory and language processing [24].…”
Section: Rehabilitation Issues In Landau-kleffner Syndromementioning
confidence: 99%
“…It has also been used to remove ballistocardiogram and ocular artefact which are the two mainly artefacts contaminating EEG data recorded during MRI scan. In LKS and ESES/CSWS EEG, source analysis applied to magneto-encephalographic data has shown a bilateral spikes generator in or propagate to the perisylvian cortex [40, 41]. …”
Section: Eses/csws New Techniques: Understanding Pathophysiologymentioning
confidence: 99%